Refiguring Museums. Investigating Tensions in Exhibition Spaces - Sarah Etz; Séverine Marguin; Henrike Rabe (Museum & Society, 2024)
Understood as active in the mediation of knowledge and values, museum spaces have become a growing field of investigation in the course of the spatial turn within the museum studies. In this special issue, we focus on the transformation of museum space. To this end, we introduce a specific theoretical framework, the refiguration of spaces, which aims to think spatial transformation in a non-linear, multiscalar and multiple way: The basic assumption is not to presume a sequential historic transformation of spatial figurations of museums – from chambers of wonders, through universal museums and white cubes towards interactive museums – in which a new type always replaces the previous one, but rather to draw our attention onto the dense juxtaposition of these figurations, which continue to be drawn upon, competing to reshape museums, and informing our spatial understanding of the museum of the future. In this editorial, we firstly (re)trace the different spatial-aesthetic figurations of museums and work out the limitations of a transformational framework. We introduce then the refiguration theory and its potential, before presenting the seven contributions of the special issue and synthesising their findings about the conflicting and shifting multiple spatialities of museums. We end our editorial with a speculative reflection about the futures of refiguring museums.